FREQUENCY OF ACUTE KIDNEY INJURY IN CASES OF LIVER CIRRHOSIS: A CROSS-SECTIONAL STUDY - KHALIL, H; KHAN, AS; AHMAD, W; AHEED, B; OWAIS, M; CHANDIO, R (Biological and Clinical Sciences Research Journal, 2024)
Acute kidney injury (AKI) frequently complicates the clinical course of liver cirrhosis, impacting patient outcomes significantly. Understanding the epidemiology of AKI in this population is crucial for timely intervention and management. Objective: To assess the frequency and clinical outcomes of acute kidney injury in patients with liver cirrhosis. Methods: Following ethical approval, this descriptive cross-sectional study was conducted at the Department of Nephrology from December 2023 to June 2024. A total of 231 patients aged 18 years and older with a confirmed diagnosis of liver cirrhosis were included. The frequency of AKI was determined using standard criteria. Data analysis was performed using SPSS 24, employing Independent samples t-tests to evaluate differences between patients with and without AKI, with a significance level set at P < 0.05.Results: Among the 231 cirrhotic patients (mean age: 52.5±10.61 years; 83.1% male), AKI was identified in 55 patients (23.8%). Patients with AKI exhibited higher mean serum creatinine (2.99±0.44 mg/dL) and blood urea nitrogen (66.64±9.92 mg/dL), along with lower sodium levels (129.37±4.14 mmol/L) and elevated total bilirubin (5.23±1.37 mg/dL) compared to their non-AKI counterparts. The average length of hospital stay was significantly longer for AKI patients (14.35±3.22 days) compared to non-AKI patients (7.37±1.92 days), and mortality was higher in the AKI group (12.7% vs. 1.7%). Conclusion: Our study highlights a significant prevalence of AKI among patients with liver cirrhosis, particularly affecting those with viral hepatitis B and C. The findings emphasize the need for vigilant monitoring and early therapeutic interventions in this vulnerable population to improve outcomes.